Distribution and Sea-to-air Flux of Nitrous Oxide in the East China Sea during the Summer of 2013. (15th July 2016) - Wang, Lan; Zhang, Guiling; Zhu, Zhuoyi; Li, Jia; Liu, Sumei; Ye, Wangwang; Han, Yu
Abstract: Dissolved nitrous oxide (N2 O) at different depths of 73 stations in the Changjiang (Yangtze River) Estuary and the East China Sea (ECS) were determined from August 4 to 31 of 2013, and the sea-to-air fluxes of N2 O were also estimated in this study. N2 O concentrations in the surface waters ranged from 6.33 to 44.40 nmol L −1 with an average of (9.27±4.30) nmol L −1 and the values in the bottom waters ranged from 5.19 to 26.98 nmol L −1 with an average of (11.87±3.71) nmol L −1 . The concentrations of N2 O decreased with distance from the Changjiang Estuary to the open sea. The vertical distributions of N2 O indicated great spatial variations. A region of significant bottom-water hypoxia, with oxygen concentration less than 1.5 mg L −1, occurred at the north of the ECS, and increased bottom N2 O concentrations was observed. Frequent vertical mixing may enhance the emission of N2 O from this hypoxic area. N2 O in the surface waters of all stations were over-saturated, and the N2 O saturations ranged from 106% to 658%, with an average of (149±62)%. We estimated the sea-to-air fluxes of N2 O as (30.6±59.1) μmol m −2 d −1 from the Changjiang Estuary, (9.8±8.8) μmol m −2 d −1 from the coastal and shelf, and (21.0±12.7) μmol m −2 d −1 from the continental slope using the Wanninkhof 1992 equation, (24.9±47.2) μmol m −2 d −1, (8.0±6.7) μmol m −2 d −1 and (16.5±9.6) μmol m −2 d −1 using the Nightingale 2000 equation, respectively. N2 O emission from the ECS was estimated to be about (8.2-16.0)×10 −2 Tg-N2 O yr −1, suggesting that the ECS was a significant net source of atmospheric N2 O. Highlights: N2 O in the Changjiang (Yangtze River) Estuary and the East China Sea (ECS) were determined from August 4 to 31 of 2013. N2 O emission from the ECS was estimated to be about (8.2-16.0)×10 −2 Tg yr −1, suggesting that the ECS was a significant net source of atmospheric N2 O. Frequent vertical mixing may enhance the emission of N2 O from the hypoxic area.